Ways to extract protein from Spirulina - Nuriddinov Abdulmuiz Nuriddin o`g`li; Mahmiyev Daler Nizomjon o`g`li; Alamova Fariza Ashrafovna; Nazarova Mahbuba Erkin qizi ass. (Peerian Journals Publishing, 2022)
Algae and microalgae are rich in biologically active compounds such as proteins, lipids, carotenoids, pigments, phenols and polysaccharides. This makes them a widely used natural material for the production of extracts, for food and food additives. Commonly used types of algae for food additives are mainly Arthrospira, Spirulina, Hematococcus Pluvialis, and Ulva. Microalgae are a good source of high-quality proteins, lipids, polysaccharides, vitamins and antioxidants. Based on this, we need to develop new versions of obtaining and extracting proteins, fats and carbohydrates
Keywords: microalgae; protein; Spirulina; Arthrospira